The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1302/0301-620x.100b3.bjj-2017-0733.r2
|View full text |Cite
|
Sign up to set email alerts
|

Biological augmentation of graft healing in anterior cruciate ligament reconstruction

Abstract: There is extensive preclinical research supporting the use of biological therapies to augment ACLR. Further clinical studies that meet the minimum standards of reporting are required to determine whether emerging biological strategies will provide tangible benefits in patients undergoing ACLR. Cite this article: Bone Joint J 2018;100-B:271-84.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
75
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(83 citation statements)
references
References 139 publications
1
75
0
7
Order By: Relevance
“…As seen in this study (Figs. , , and ), ligament reconstructions where a tendon is passed through a bone tunnel, such as the femoral and tibial tunnels in an ACL reconstruction procedure, can yield zonal attachments of the tendon graft to the adjacent bone . Therefore, ligament reconstructions can be used to study the mechanisms of zonal tendon‐to‐bone repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in this study (Figs. , , and ), ligament reconstructions where a tendon is passed through a bone tunnel, such as the femoral and tibial tunnels in an ACL reconstruction procedure, can yield zonal attachments of the tendon graft to the adjacent bone . Therefore, ligament reconstructions can be used to study the mechanisms of zonal tendon‐to‐bone repair.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, healing following tendon‐to‐bone repair results in disorganized scar formation rather than re‐establishment of zonal tendon‐to‐bone attachments. In contrast, when a tendon is placed through a bone tunnel, zonal attachments with collagen fibers spanning across unmineralized and mineralized fibrocartilage occur . While direct tendon repairs typically are not performed through a bone tunnel (due to anatomic constraints), ligament reconstructions often utilize a tendon graft placed though bone tunnels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings remind us that whether it is synovitis or infection, graft failure may occur. Hexter et al reviewed a great deal of preclinical research that supported the use of biological augmentation in ACLR [24], and the biologic augmentation might be beneficial in a graft such as LARS that depends on ingrowth tissue. This may be the direction of future research.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that show no difference in clinical outcomes by addition of PRP. [41,42] In a very recent systematic review investigating the usage of PRP, bone substitutes, calcium phosphate-hybridized grafts, and autologous stem cells, Hexter et al, [43] concluded that most of the studies are preclinical and there is still a need for extensive clinical studies to support their use.…”
Section: Bonementioning
confidence: 99%